Cocaine - Characteristics and addiction - Katarzyna Girczys-Połedniok; Robert Pudlo; Magdalena Jarząb; Agnieszka Szymlak (Nofer Institute of Occupational Medicine, 2016)
Cocaine use leads to health, social and legal problems. The aim of this paper is to discuss cocaine action, addicts characteristics, use patterns and consequences, as well as addiction treatment methods. A literature review was based on the Medline, PubMed, Polish Medical Bibliography databases and the Silesian Library resources. The Police and Central Statistical Office statistics, as well as the World Health Organization, the European Monitoring Centre for Drugs and Drug Addiction and the National Office for Combating Drug Addiction reports were used. Cocaine leads to mood improvement, appetite decrease, physical and intellectual activity enhancement, euphoria, inflated self-esteem, social networking ease and increased sexual desire. Cocaine hydrochloride is mainly used intranasaly, but also as intravenous and subcutaneous injections. Cocaine use and first addiction treatment fall in later age compared to other psychoactive substances. There is a high men to women ratio among addicts. There is a relationship between cocaine addiction, the presence of other disorders and genetic predisposition to addiction development. Polish reports indicate higher popularity of cocaine among people with a high economic and social status. Although Poland is a country with the low percentage of cocaine use, its popularity is growing. The consequences of cocaine use concern somatic and mental health problems, socioeconomic and legal conditions. The drug plays a role in crimes and traffic accidents. Because of the risks associated with cocaine use, it has been listed in a register of drugs attached to the Act on Counteracting Drug Addiction. Addiction treatment includes psychological, pharmacological and harm reduction strategies. Med Pr 2016;67(4):537-544